Editor's Note = Note du directeur [4, May 1979] - Kealey, Gregory S. (Labour / Le Travail, 1979)
Highlights the expansion of the documents section of the journal and the inauguration of a new section on literature reviews. Invites wider contributions to the journal (poetry, fiction, theatre, musical recordings) and debates, as illustrated by Paul Craven's response in the issue to Reg Whitaker's article on Mackenzie King that was previously published in the journal. The volume is in memoriam of H.C. Pentland, whose article on the 1972 survey of the Canadian industrial relations system is published for the first time.

H.C. Pentland and Working Class Studies - Kealey, Gregory S. (Canadian Journal of Political and Social Theory, 1979)
Analyzes Pentland's pathbreaking contributions to Canadian history and political economy.